387 Trauma through the years; a comparison of injury patterns and interventions between adolescent, adult, and paediatric trauma cases. (17th August 2022) - Mullen, Stephen; Tolson, Amy; Bouamra, Omar; Watson, Ben; Lyttle, Mark; Roland, Damian; James, David
Abstract : Aims: Adolescent trauma patients transition through services and dependent on age, may be managed in either paediatric, adult or mixed trauma departments. Clinicians are posed with a dilemma whether to follow adult or paediatric trauma guidelines. There is currently little in the way of published studies which compare adolescent (10-24) trauma patterns and interventions to adult (³25) or paediatric (<10) data. Methods: Data were collected from the national Trauma and Audit Research Network (TARN) database for all adolescent trauma episodes in England, Wales and Northern Ireland over a 10-year period (January 2010 to December 2019). The aim is to compare adolescent trauma patterns and interventions to adult and paediatric cases. We performed direct comparison of demographics and analysis of continuous variables with Mood's test. Results: A total of 505, 162 TARN cases were included. A number of trauma descriptors or outcomes were more prevalent in adolescent group. Road traffic accidents are the most common mechanism of injury in the adolescent group, in contrast to both the paediatric and adult group where falls <2m were most common. Violence related injury (shootings and stabbings) were also more common in the adolescent group; 9.4% compared with 0.3% and 1.5% in the paediatric and adult groups respectively. The adolescent grouping had the highest median injury severity score and the highest proportion of interventions (blood products, chest drain insertion, thoracotomy and cricothyroidotomy). The adolescent group also often encapsulated trends occurring due to increasing age. The proportion of cases due to stabbing peaks at 17 (11.8%), becoming the second most common MOI. The median ISS remains at 9 until aged 15, peaking at 13 in 18-year-olds. The percentage of cases that fulfil the definition of polytrauma enters double figures (11.8%) at 15 reaching a peak of 17.6% at age 18. The use of blood products within the first 6 hours remains around 2% (1.6-2.8%) until 15 (3.4%), increasing to 4.7% at age 16. Chest drain insertion peaks at 9.6% at age 17. Conclusion: Trauma patterns are more closely aligned between adult and paediatric cohorts, than adolescence with our results suggesting they are a unique entity. However, there is considerable change during adolescence meaning the common division of paediatric to adult trauma care at 16 years to be an imperfect but not unreasonable service model. Training, trauma resources and responses need to be implemented with the adolescent group in mind with specific consideration for targeted prevention given the different predominant mechanisms of injury in this group.